Agro-morphological Variability of Barley under Normal and Late Sown Conditions in Chitwan, Nepal - Poudyal, Chiranjibi; Pathak, Santosh; Ojha, Bishnu Raj; Marahatta, Santosh (Journal of Nepal Agricultural Research Council, 2019)
Agro-morphological traits serve as an indirect selection criteria for developing new cultivars with superior performance ability. In order to study variability of agro-morphological traits of exotic barley genotypes under normal and late sown conditions, a field experiment was conducted at the research field of Institute of Agriculture and Animal Science, Chitwan, Nepal in 2015. Altogether, 13 genotypes of barley were sown under two factor factorial RCBD with three replications in two dates. Normal sowing was done on 29 Nov 2014 while late sowing was done on 1 Jan 2015. Agro-morphological traits were found to be varying significantly in late sowing condition as compared to normal one. The mean number of days to booting and heading reduced by 15.19% and 9.64%, respectively in late sown condition. Similarly, plant height reduced by 19.53%, peduncle length by 16.62%, flag leaf width by 42.87%, flag leaf area by 36.44% and FL-1 leaf area by 36.51% in late sown condition. Biomass, grain yield and harvest index were also found to be reduced by 39.66%, 69.77% and 46.48%, respectively for late sowing condition. Nepalese landrace Soluwa performed better in normal sown condition while exotic genotype SBYT 14-1 performed better in late sown condition. SBYT 14-27 and SBYT 14-38 genotypes exhibited stable yield in both sowing conditions. Stability attribute provides an avenue for further study of such promising genotypes from agronomic and breeding perspectives under varying edaphic and agronomic conditions, and also open up the possibility of developing best performing cultivar of barley for lower plain region of the country.